KONSEP HARTA PERSPEKTIF MAQASID AL-SYARIAH DAN IMPLEMENTASINYA PADA WAKAF TUNAI - Ariani Hidayat (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Cash waqf is one of the instruments to empower the potential of public funds with the aim of alleviating poverty and other socio-economic problems. The substance of cash waqf is in line with the maqasid alshari'at which leads to al-maslahah al-mursalah (universal benefit) one of them is in order to realize social welfare through justice of income and wealth distribution. In addition, one of the implementation of maqasid al-syari'at contained in cash waqf is the principle ta'awun (mutual help) to the less fortunate.